Discovering the Rights Model : an analysis of kinship and caste in rural Ceylon - Gamburd, Geraldine DeNering; Social Scientists Association of Sri Lanka (Colombo : Social Scientists' Association, 2009)
With reference to Salagama caste of Bopitiya, Sri Lanka in 1960's.
Originally presented as the author's thesis (doctoral)--Colombia University, 1972.
Keywords: Salagama -- Kinship -- Sri Lanka -- Bopitiya; Salagama -- Sri Lanka -- Bopitiya -- Social life and customs -- 20th century; Kinship -- Sri Lanka -- Bopitiya; Caste -- Sri Lanka -- Bopitiya; Bopitiya (Sri Lanka) -- Social life and customs -- 20th century